Subcutaneous gentamicin injection around the cuff in treatment of resistant exit site infection in peritoneal dialysis patients: a pilot study - Dizdar OS; Ozer O; Erdem S; Gunal AI (Dove Medical Press, 2017)
Oguzhan Sıtkı Dizdar,1 Ozerhan Ozer,2 Selahattin Erdem,2 Ali Ihsan Gunal3 1Department of Internal Medicine and Clinical Nutrition, Kayseri Training and Research Hospital, Kayseri, Turkey; 2Department of Internal Medicine, Kayseri Training and Research Hospital, Kayseri, Turkey; 3Department of Internal Medicine Division of Nephrology, Kayseri Training and Research Hospital, Kayseri, Turkey Background/purpose: One of the most common complications of the peritoneal dialysis (PD) is the infection of the exit site of the peritoneal catheter. The aim of the present study was to evaluate the efficacy of the subcutaneous gentamicin injection around the cuff as a part of routine treatment of the resistant exit site infection (ESI).Methods: If the exit site remains infected after a 2-week systemic antibiotics treatment, it is defined as resistant ESI. In these cases, systemic antibiotics were discontinued and a subcutaneous 40-mg gentamicin injection was administered around the external cuff of the PD catheter every 3 days. A total of three or four injections were given to each patient.Results: A subcutaneous gentamicin injection was administered around the cuff in thirteen patients for the treatment of resistant ESI over a 2-year period. The median follow-up time in cured patients was 12 months. Eleven of the thirteen patients had been apparently cured of their resistant ESI, with no recurrence. None of the patients had a gentamicin-resistant species. Subcutaneous gentamicin-related adverse effect was not observed in any patient.Conclusion: Subcutaneous gentamicin injection around the cuff is a well-tolerated and effective strategy for treating resistant ESI. To gain widespread approval of this therapy and reach a consensus about ESI management, additional studies are needed. Keywords: peritoneal dialysis, subcutaneous gentamicin, local treatment, catheter, efficacy